The effects of exercise duration on the dynamics of respiratory gas exchange, ventilation and heart rate - Solomon, C.; Taylor, N. A. S. (European Journal of Applied Physiology, 1994)
This study investigated the effect of exercise duration on the response dynamics of oxygen consumption (VO2), carbon dioxide output (VCO2), ventilation VE), and cardiac frequency (fc) following stepped changes in exercise intensity, by manipulating the duration of the pretransition exercise period. A group of 11 healthy men performed a stepped exercise intensity cycling protocol on three separate occasions, each consisting of a stepped increase from 55% to 65% peak oxygen consumption (VO2,peak) of 6-min duration, followed by a stepped decrease to 55% VO2,peak of 10-min duration. This stepped protocol was preceded by either 5, 15, or 60 min of cycling at 55% VO2,peak. The response times for each variable were calculated at 10% increments between the prestep baselines and poststep plateaux. Following the stepped increase, the response times for VO2 at the 50%, 60%, 70%, 80%, and 90% relative increments were significantly reduced in the 60-min condition compared to the 15-min condition (P < 0.05); however, the response times for VCO2, VE, and fc were not significantly altered across the three conditions. No significant differences were found in the response times for VO2, VCO2, VE, and fc, across the three conditions following the stepped decrease in exercise intensity. It was concluded that the faster response time of aerobic metabolism to a stepped increase in exercise intensity was mediated by increases in active muscle temperature, leading to improved oxygen utilisation